Hsp90 molecular chaperone: structure, functions and participation in the cardio-vascular pathologies - Kroupskaya, I.V. (Вiopolymers and Cell, 2009)
This review is devoted to analysis of structural and functional properties of molecular chaperon Hsp90. Hsp90 are highly widespread family of heat shock proteins . Protein is found in eubacteria and all branches of eukarya, but it is apparently absent in archaea. It is one of key regulators of numerous signalling pathways, cell growth and development, apoptosis, induction of autoimmunity and progression of heart failure. The full functional activity of Hsp90 shows up in a complex with other molecular chaperones and co-chaperones. Molecular interactions between chaperones, different signaling proteins and protein-partners are highly crucial for the normal functioning of signaling pathways and its destruction are causes the alteration of cell physiology up to its death. Обзор посвящен анализу структурных и функциональных свойств молекулярного шаперона Hsp90. Hsp90 является представителем широко распространенного семейства белков теплового шока. Он обнаружен в бактериях и в эукариотах, но отсутствует в архебактериях, служит также одним из ключевых регуляторов многочисленных сигнальних путей, определяющих рост и развитие клеток, апоптоз, индукцию аутоиммунных реакций и прогрессию сердечной недостаточности. Полная функциональная активность этого белка проявляется в комплексе с другими молекулярними шаперонами и кошаперонами. Молекулярные взаимодействия между шаперонами, различными сигнальными белками и белками-партнерами критичны для нормального функционирования сигнальных путей, а нарушение их вызывает изменения в физиологии клетки вплоть до ее гибели. Огляд присвячено аналізу структурних і функціональних властивостей молекулярного шаперону Hsp90. Hsp90 є представником широко розповсюдженої родини білків теплового шоку. Його знайдено в бактеріях та в еукаріотах, але він відсутній в архебактеріях, є одним із ключових регуляторів багаточисельних сигнальних шляхів, які обумовлюють ріст і розвиток клітин, апоптоз, індукцію автоімунних процесів і прогресію серцевої недостатності. Повна функціональна активність цього білка виявляється у комплексі з іншими молекулярними шаперонами та кошаперонами. Молекулярні взаємодії між шаперонами, різноманітними сигнальними білками і білками-партнерами критичні для нормального функціонування сигнальних шляхів, а їхнє порушення призводить до змін у фізіології клітини і навіть до її загибелі.